Kemampuan Pemecahan Masalah Melalui Pembelajaran Interactive Demonstration Siswa Kelas X SMA pada Materi Kalor - Rismatul Azizah; Lia Yuliati; Eny Latifa (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2016)
The application of teacher centered learning in classroom is causing the underdevelopment of students problem solving ability and students activity in learning. Interactive demonstration is an active learning model developed by Wenning. Through interactive demonstrations, students can use the basic intellectual process skills that includes predicting, explaining, estimating, acquiring and processing data, formulating and revising scientific explanations using logic and evidence, and recognizing and analyzing alterative xplanations and models. The purpose of this research is to determine the effect of interactive learning demonstration toward students' problem solving ability. This research was mixed method research with embedded design. The sample is selected by purposive sampling method, that was the grade X MIA 1 students of SMAN 1 Bangil. The results of this study indicate that there is the effect of interactive demonstration learning and that learning can enhance students' problem-solving abilities.